2019
DOI: 10.1021/acsami.9b08198
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Doped Hybrid Carbon Nanotube–Graphene Wires

Abstract: The following paper explores the nature of electronic transport in a hybrid carbon nanotube–graphene conductive network. These networks may have a tremendous impact on the future formation of new electrical conductors, batteries, and supercapacitors, as well as many other electronic and electrical applications. The experiments described show that the deposition of graphene nanoflakes within a carbon nanotube network improves both its electrical conductivity and its current-carrying capacity. They also show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…Interestingly, the authors have also demonstrated that the conductivity scales inversely proportionally to the CNT diameter for an ideal fiber. Barnett et al (2019) and Lepak-Kuc et al (2019) have shown via experimental and theoretical approaches the dependence of the electrical contact resistance at the junction regions between CNTs (SWCNTs and/or MWCNTs) and between CNTs and graphene interfaces by considering morphology, structure (i.e., chirality). Interestingly, it was shown that when there is a large…”
Section: Highly Electrically Conductive Metal-less Conductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the authors have also demonstrated that the conductivity scales inversely proportionally to the CNT diameter for an ideal fiber. Barnett et al (2019) and Lepak-Kuc et al (2019) have shown via experimental and theoretical approaches the dependence of the electrical contact resistance at the junction regions between CNTs (SWCNTs and/or MWCNTs) and between CNTs and graphene interfaces by considering morphology, structure (i.e., chirality). Interestingly, it was shown that when there is a large…”
Section: Highly Electrically Conductive Metal-less Conductorsmentioning
confidence: 99%
“…On the other hands, the addition of graphene flakes within a CNT wire to constitute a hybrid composition has been shown to increase the electrical conductivity, current-carrying capacity (or ampacity, which can be defined as the maximum current in amperes, that a conductor can carry continuously under the conditions of use and without exceeding its temperature rating) and doping properties (Li and Pandey, 2015;Lepak-Kuc et al, 2019). Besides the remarked relevance of the graphene flake characteristics, of the fiber purity and of the solvent properties, the authors explained that graphene flakes constitute effective bridges by means of a theoretical model.…”
Section: Referencesmentioning
confidence: 99%
“…There have been advances in fabricating nanocomposites composed of a multiphase solid materials, where one of the dispersed phases is in the nanometer-scale dimension [ 19 ] and the other is a major phase, such as ceramic, metals, or polymers [ 20 ]; carbon-carbon composites [ 21 ] and nanocarbon [ 22 ] are combined as a matrix material.…”
Section: Role Of Significant Nanocomposites In Drilling Fluidsmentioning
confidence: 99%
“…This treatment can, at the same time, decrease the specific surface area/porosity [22,31,32]. Another example of this post-manufacture processing is purification and doping of fibers/films, e.g., by annealing and acid/halogen infiltration [46][47][48][49][50]. These post-treatments are conducted to achieve improvements in the performance of the CNT material and not any change in its actual function.…”
Section: Use Of As-made Cnt Fibers and Filmsmentioning
confidence: 99%
“…Thin and thick CNT films used for flexible transparent electrical components and 3D shaped structures respectively were produced via the FC-CVD method according to the method reported before [46,47]. Luminescent capacitors were produced using CNT fibers rolled from FC-CVD CNT films and condensed via acetone, of 150 µM in diameter.…”
Section: Cnt Fibers and Filmsmentioning
confidence: 99%